2013
DOI: 10.1590/s0104-11692013000700019
|View full text |Cite
|
Sign up to set email alerts
|

Nursing workload and patient safety - a mixed method study with an ecological restorative approach

Abstract: Objective: The aim of this study was to analyze the potential association between nursing workload and patient safety in the medical and surgical inpatient units of a teaching hospital.Method: a mixed method strategy (sequential explanatory design). Results: the initial quantitative stage of the study suggest that increases in the number of patients assigned to each nursing team lead to increased rates of bed-related falls, central line-associated bloodstream infections, nursing staff turnover, and absenteeism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1
25

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 18 publications
2
82
1
25
Order By: Relevance
“…In research (19) performed in the admission units of the same hospital headquarters as the present study, adopting the same statistics, it was identified that the increase in the number of patients per nursing professional is associated with an increase in the rates of falls from bed, venous catheter-related bloodstream infections, and absenteeism. Although postulated that a worse rate of patients per nursing professional or other professionals (radiology technicians, nutrition attendants) would be associated with delays in the process of indication of tube use, this hypothesis was not confirmed in any of the stages.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In research (19) performed in the admission units of the same hospital headquarters as the present study, adopting the same statistics, it was identified that the increase in the number of patients per nursing professional is associated with an increase in the rates of falls from bed, venous catheter-related bloodstream infections, and absenteeism. Although postulated that a worse rate of patients per nursing professional or other professionals (radiology technicians, nutrition attendants) would be associated with delays in the process of indication of tube use, this hypothesis was not confirmed in any of the stages.…”
Section: Discussionmentioning
confidence: 75%
“…Although postulated that a worse rate of patients per nursing professional or other professionals (radiology technicians, nutrition attendants) would be associated with delays in the process of indication of tube use, this hypothesis was not confirmed in any of the stages. In fact, the care units included in the previously cited study (19) have a fixed number of patients, which does not happen in the emergency department, where overcrowding is a constant. Also, the types of outcomes evaluated, which were not about delays in unit of time (minutes), can explain the difference among these findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both factors are associated with patient safety, being considered as issues widely discussed in the health area, with resources being mobilized by the WHO (1) . According to some authors, the scarce labor force in the area of Nursing in some countries, the lack of training, and the excessive workload are problems that directly compromise patient safety (7)(8)(9)(10) .…”
Section: Discussionmentioning
confidence: 99%
“…The researchers used the triangulation of methods for the analysis of safety culture on the perception of nurses and of records on hospital documents, such as records of Nursing occurrences book. The instruments used were (1) Sociodemographic and occupational questionnaire, (2) Hospital Survey on Patient Safety Culture (HSOPSC), (3) Semi-structured interview script, and (4) Checklist for analysis of events related to patient safety in nursing records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation